Compression and Flexural Strength of Bone Cement Mixed with Blood. (August 2016) - Tan, JH; Koh, Bryan TH; Ramruttun, AK; Wang, Wilson
Purpose: To assess the compression and flexural strength of bone cement mixed with 0 ml, 1 ml, or 2 ml of blood. Methods: High viscosity polymethyl methacrylate (PMMA) loaded with or without gentamicin was used. Blood was collected from total knee arthroplasty patients. In the same operating room, one pack of cement each was mixed with 0 ml (control), 1 ml, or 2 ml of blood for 1 minute during the dough phase. The dough was extruded into cylindrical and rectangular moulds for 20 minutes of setting, and then cured in phosphate buffered saline at 37±1°C for 7 days. The samples were visually inspected for fractures and areas of weakness, and then scanned using micro-computed tomography. 48 gentamicin-loaded and 59 non-gentamicin-loaded samples mixed with 0 ml (control), 1 ml, or 2 ml of blood were randomised for flexural and compression strength testing; each group had at least 6 samples. Results: In samples loaded with or without gentamicin, the flexural and compressive strength was highest in controls, followed by samples mixed with 1 ml or 2 ml of blood. In samples mixed with 2 ml of blood, the flexural strength fell below the standard of 50 MPa. In samples mixed with 2 ml of blood and all gentamicin-loaded samples, the compressive strength fell below the standard of 70 MPa. Micro-computed tomography revealed areas of voids and pores indicating the presence of laminations and partitions within. Conclusion: The biomechanical strength of PMMA contaminated with blood may decrease. Precautions such as saline lavage, pack drying the bone, change of gloves, and prompt insertion of the implant should be taken to prevent blood from contaminating bone cement.